Technological connections in the development of 18th and 19th century Chinese painted enamels. (April 2022) - Norris, Dana; Braekmans, Dennis; Shortland, Andrew
Highlights: Chinese painted enamel technology is derived from traditions in China and Europe. The balance of glass formers is an amelioration of Chinese cloisonné enamel. Arsenic opacification supersedes the use of fluorite in Chinese enamels. The broad palette combines technologies of traditional and foreign colourants. Abstract: Chinese painted enamel is an artistic tradition of enamelled copperwares developed during the Kangxi period (1662–1722), commonly referred to as Canton enamel after the Wade-Giles spelling of Guangzhou. In this study, enamel fragments from areas of damage in the decorated surface of ten Chinese painted enamel objects dating to the 18th and early 19th century in the collections of the Ashmolean and Fitzwilliam Museums were non-destructively analysed with ESEM-EDX (Environmental Scanning Electron Microscopy - Energy Dispersive X-Ray Spectroscopy). After analysis, the enamel fragments were reattached to the objects using a conservation grade adhesive. Quantitative EDX elemental analysis is presented for the white enamel, underdrawings, eight painted enamel colours, outlines, and gilding. The enamel-glass composition, opacifier and colourants are discussed and compared to ceramic, glass, and enamelled metal technologies in use during the Ming Dynasty (1368–1644). The results show that Chinese painted enamels combine Chinese and European technology to create a new and distinct art form.